GEOLOGY AND 3D RESERVOIR MODEL OF LAHAT FORMATION CASE STUDY B2 LAYER BERBAKAT FIELD SOUTH SUMATRA BASIN - Rachman, Faisal
The Berbakat (BKB) field, operated by PT Pertamina EP Asset 2, Field Pendopo, is situated around 160 km west of Palembang, the provincial capital of South Sumatra. With an initial production rate of 1,835 BOPD, this field began producing oil in 1932. The Talang Akar Formation's (TAF) layer 1st and 2nd and the Lahat Formation (LAF) layer B2 is the BKB’s primary reservoirs. With a recovery ratio of 32.3%, the cumulative production in the TAF Formation is 147.4 MMBO, but in the LAF Formation, it is 2.1 MMBO with a recovery factor of 2.3%. According to these findings, the LAF layer still has a significant amount of oil potential. Hence a detailed reservoir model which previously doesn’t exist is required to boost production in this layer. The study employed core rock data from two wells, 219 wireline data, fossil analysis from two wells. The investigation was carried out in stages, with the help of bio stratigraphic data to establish the depositional environment and age, lithofacies and facies connections using core rock data. Furthermore, the parasequence and sequence markers was identified from each well's electro facies pattern, the research cintinued by making a geological modell including facies and property. As the result from core sample, the facies of LAF consist of shale, siltstone, tuff and sandstone. Three electrofacies were identified, there are: aggradational pattern reflecting a braided river belt deposit, fining upward pattern as a floodplain deposit, and coarsening upward pattern as crevasse splay deposit. Sequence stratigraphy analysis resulting two sequence those are: SB0-SB-1 transgressive system tact, and SB-01 – MFS-01 Lowstand system tract and facies architecture as a braided channel belt, crevasse splay and floodplain. Geological model shows a relative deposition direction affected by graben orientation, therefor the direction of fluvial braided system trending from north to south, and is believed to be Early Oligocene in age. Average porosity for Layer B2 is 0.17, average permeability is 43.4mD, and average thickness is 25.2 ft, and those properti distribution are contolled by depositional environment.